An innovative face emotion recognition-based platform by using a mobile device as a virtual tour - Patrono, Luigi; Podo, Luca; Rametta, Piercosimo (2019)
Emotions are the base of human evolution. They help us to survive and to face up all problems of our life. Without emotions human evolution was not possible and we would be in caves. Nowadays, emotions are a very important aspect in different field not only in psychology. They are very important to understand human mind and decision-making process.Emotional tourism is an example of a new way to use emotions analysis. In this field emotions are used to create a most deep experience from the begin of a travel to each steps of the journey. They help tourism to make traveler the protagonist of his travel and not just a spectator.In this paper, we are going to show an app which predicts a travel destination based on user’s mood and facial expressions to specifics visual and auditory trigger to encounter his reactions. This app uses different technology linked together to make this solution versatile and dynamic. It implements different technology modules to perform facial and mood analysis, capturing the image, store image and show all trigger to the user. By adopting this solution is possible to easily upgrade the app and each module can be changed with no large problem adapting it to the current version of the app.
Bibliografija: 20 jed.
Summary.
Keywords: Mobilni uređaji -- Aplikacije -- Emocije